Dialogic Discourses of French and English in Acadie - McElgunn, Hannah (Minorités linguistiques et société / Linguistic Minorities and Society)

(untitled) (Institut canadien de recherche sur les minorités linguistiques / Canadian Institute for Research on Linguistic Minorities, 2017)
Debate in the Acadian media over the quality of the French language is a recurrent aspect of sociolinguistic life in this region of French Canada. In the fall of 2012, this debate was relaunched by an incendiary newspaper column, written by a Quebec-based journalist, questioning whether the French spoken by young Acadian musicians was really a language at all. Based on twelve interviews conducted shortly after this debate, this article examines how university students in Acadie take up these media discourses about the quality of the French language. In general, the students interviewed regarded the French language as inherently rule-bound and structured, in contrast to English, which many held to be comparatively without rules, even easygoing. The author suggests that this particular view has developed in part because of exposure to discussion over the quality of French in Acadie, and that any attempt to improve what is perceived as the poor quality of French in Acadie cannot ignore the very terms in which it portrays the French language. These figurations become part of the linguistic ideologies of young French speakers in Acadie and potentially feed into the very state of affairs that commentators lament.